(untitled) (Damascus University Journal of agriculture sciences, 2023)
This study was conducted in the laboratories of the Department of Food Sciences, Faculty of Agricultural Engineering. It aimed to study the possibility of using two types of water raisin extracts (black raisin and white zein raisin) to fortify yoghurt with three percentages (1%, 2%, 3%), with the aim of knowing the effect of the antioxidant properties present in raisins on the growth of bacteria Lactobacillus acidophilus and its activity, which were added to raisin extracts in different proportions (0.5%, 1%, 2%). The results showed that the highest growth of L. acidophilus was when mixed with 2% raisin extracts. In the second phase of the research, raisin extract fortified with 2% was used to manufacture curd samples with an addition of this extract (1,2%, 3%). The results showed that the addition of both the black currant extract and the white zeini raisin extract, led to an increase in the acidity, pH of samples and ash, in addition to an increase in the number of L. acidophilus bacteria, as well as an increase in the activity of inhibiting free radicals (measuring the antioxidant activity of DPPH). It was accompanied by a slight increase in the percentage of moisture, while the percentage of fat in the milk was not affected by these additives, and they had no effect on the sensory properties of the studied samples. The samples content of black raisin extract outperformed samples containing white raisin extracts, especially in the highest percentage of addition, which amounted to 3%, in terms of the high number and vitality of L. acidophilus bacteria and in terms of high antioxidant activity (DPPH%) for a storage period of 30 days. It was also noted that there are differences between the control sample and the rest of the samples fortified with bacteria and aqueous raisin extracts.